Abnormal prenatal brain development in Chiari II malformation - Masse, Olivia; Kraft, Emily; Ahmad, Esha; Rollins, Caitlin K.; Velasco-Annis, Clemente; Yang, Edward; Warfield, Simon Keith; Shamshirsaz, Alireza A.; Gholipour, Ali; Feldman, Henry A.; Estroff, Judy; Grant, Patricia Ellen; et al. (Frontiers in Neuroanatomy, 2023)
Introduction The Chiari II is a relatively common birth defect that is associated with open spinal abnormalities and is characterized by caudal migration of the posterior fossa contents through the foramen magnum. The pathophysiology of Chiari II is not entirely known, and the neurobiological substrate beyond posterior fossa findings remains unexplored. We aimed to identify brain regions altered in Chiari II fetuses between 17 and 26 GW. Methods We used in vivo structural T2-weighted MRIs of 31 fetuses (6 controls and 25 cases with Chiari II). Results The results of our study indicated altered development of diencephalon and proliferative zones (ventricular and subventricular zones) in fetuses with a Chiari II malformation compared to controls. Specifically, fetuses with Chiari II showed significantly smaller volumes of the diencephalon and significantly larger volumes of lateral ventricles and proliferative zones. Discussion We conclude that regional brain development should be taken into consideration when evaluating prenatal brain development in fetuses with Chiari II.